Pengaruh Gaya Kepemimpinan, Budaya Organisasi, Dan Motivasi Kerja Terhadap Kepuasan Kerja Di PDAM Bengkayang - Hilaria Rini; Pramatatya Resindra Widya (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Job satisfaction is a feeling that is very important in work. If someone has a very high level of job satisfaction then they will have positive feelings about the job. This study uses a confirmatory method with a quantitative approach, and uses primary data and secondary data for data collection methods. where the research was conducted at the PDAM Bengkayang Office with a population of 62 people using a census technique. The purpose of this study was to test and analyze the influence of leadership style, organizational culture and work motivation on job satisfaction in Bengkayang PDAM Office. Using data validity and reliability test methods, sample adequacy test (KMO), normality and multicollinearity tests, multiple linear regression analysis data are R^2 (determinant coefficient), t test (coefficient) and F test (Goodness of Fit Index) with SPSS 16.0 data processing. With the results of leadership style, organizational culture has no significant effect on job satisfaction, while work motivation has a significant effect on job satisfaction at PDAM Bengkayang Office.